(untitled) (AYUSHDHARA, 2025)
The present study documents the ethnomedicinal knowledge of plants used for gastrointestinal (GI) disorders in the Dhanaulti region of the Western Himalayas, Uttarakhand, India. A field survey conducted from 2023 to 2024, across spring, summer, and late winter, recorded 54 plant species belonging to 28 families traditionally employed for Gastrointestinal ailments. Data were collected through semi-structured interviews, group discussions, and participant observation with local healers and community members, and verified through standard floras and herbarium authentication. Among the reported species, 22 were primarily used for diarrhoea and dysentery, 11 for abdominal colic, 8 for dyspepsia and appetite stimulation, 7 for hepatic conditions, and 6 for constipation. Herbs dominated the flora (57%), followed by shrubs (24%), trees (11%), and climbers (8%). Plant parts most frequently utilized included roots (20 species), leaves (19), and fruits (13). Asteraceae was the most represented family, with nine species. Notably, 30% of the documented plants were also referenced in classical Ayurvedic literature, reinforcing their traditional applications. The findings emphasize the continued reliance of rural communities on plant-based remedies due to limited healthcare access and highlight the urgent need to conserve and validate this indigenous knowledge for future phytochemical and pharmacological research and augmenting the Ayurvedic repository.